2016
DOI: 10.1136/bcr-2016-217990
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of anti-GBM nephritis in a 90-year-old patient

Abstract: A 90-year-old woman who had bloody diarrhoea, nausea, weakness and reduced urine output was found to have acute kidney injury. Her inflammatory markers were raised and her chest X-ray suggested an inflammatory process. She was initially suspected to have acute kidney injury secondary to dehydration and sepsis but when her autoimmune screen returned positive for antiglomerular basement membrane antibodies our diagnosis and management strategy was reconsidered. This is a case report of Goodpasture disease presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Good pasture syndrome or anti-GBM glomerulonephritis, was first named by Ernest Good Pasture in 1919 (4). A little later, Lerner et al found that anti-GBM antibodies cause this abnormality (5). Anti-GBM nephritis is described as a vasculitis disorder characterised by autoantibody attack against the α3 chain of the type IV non-collagenous domain in the GBM and alveolar basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Good pasture syndrome or anti-GBM glomerulonephritis, was first named by Ernest Good Pasture in 1919 (4). A little later, Lerner et al found that anti-GBM antibodies cause this abnormality (5). Anti-GBM nephritis is described as a vasculitis disorder characterised by autoantibody attack against the α3 chain of the type IV non-collagenous domain in the GBM and alveolar basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our patient, a 91-year-old woman, was the oldest patient at the onset of anti-GBM disease described in the English literature. Prior to our patient, the oldest reported patient in the English literature was a 90-year-old woman [6]. The current recommendation for the treatment of anti-GBM disease is the early introduction of immunosuppressants and plasmapheresis [7].…”
Section: Discussionmentioning
confidence: 99%